Acquisition of the Dutch NPI Hoeven 'Need': From Lexical Frames to Abstract Knowledge. (3rd April 2018) - Lin, Jing; Weerman, Fred; Zeijlstra, Hedde
ABSTRACT: This article aims to investigate how Dutch children may eventually converge on a targetlike distribution of hoeven 'need, ' a modal verbal NPI (Negative Polarity Item), based on its appearance in the scope of merely some but not all of its possible licensers in the language input (i.e., the induction problem). Imitation performance was obtained from 106 monolingual Dutch children (2;09–5;10; mean = 4;04; SD = 8.5 months) using an elicited imitation task. Results suggest that before age 3, children only accept hoeven to appear with either the sentential negation niet 'not' or the negative quantifier geen 'no.' After age 3, children start developing their knowledge of the licensing of hoeven in other negative expressions as well—namely niemand 'nobody, ' weinig 'few, ' and alleen 'only'—and eventually allow hoeven in the scope of these negative words after age 5. Based on these developmental patterns, we assume that children initially analyze hoeven as bearing a lexical dependency with either niet or geen, represented by two lexical frames [hoef niet ] 'need not' and [hoef geen ] 'need no' and that they develop a dependency relationship between the NPI and an abstract negatorneg later on, which is realized by an abstract analysis [hoef neg ] 'needneg. ' Adopting a distribution-based learning approach, we show that the two lexical frames are established based on hoeven 's overwhelming occurrence with either niet or geen in the input. As for the development of the abstract analysis, we argue that children's knowledge of syntactic decomposition of negation is of crucial importance. Since [hoef neg ] turns out to be the representation of the NPI in late child grammar, we moreover argue that hoeven is an NPI, due to its lexical dependency with the abstract negatorneg